Insecticidal activity assessment of Thymus capitatus essential oils in combination with natural abrasives against Myzus persicae. Khaled, W., Ben Fekih, I., Chaieb, I., Souissi, R., Harbaoui, I., and Boukhris-Bouhachem, S. (Tunisia) - Wafa Khaled; Ibtissem Ben Fekih; Ikbal Chaieb; Rebha Souissi; Imen Harbaoui; Sonia Boukhris-Bouhachem (Tunisian Journal of Plant Protection, 2017)

(untitled)
This study was performed to evaluate the insecticidal activity of Thymus capitatus essential oils and two natural abrasives to control Myzus persicae. The in vitro application of thyme essential oils showed a significant toxic effect by fumigation as well as by spraying. The LC50 for both application methods recorded after 24 h were about 20.01 and 13.26 µl/l air, respectively. In addition, in vivo experiment based on bioinsecticide formulation (LC50 thyme essential oils + kaolin or diatomaceous earth) were carried out. The mortality rates registered after 24 h were 74.19 and 97.84% for the combination with kaolin and diatomaceous earth, respectively. Meanwhile, emulsions with 1 μl of these oils have been tested on the target aphid. This treatment has lead after 24 h to a mortality rate of 55.55%. The mechanical effect of both abrasive powders has been highlighted through dehydration, shrinkage and deformation of the aphid cuticle. Interestingly, the combination of diatomaceous earth with the T. capitatus essential oils was significantly the most effective to control aphid populations.